Design and implementation of a 2.4 ghz embedded RFID system for fruit maturity evaluation for agricultural industries utilizing wireless mesh sensor network - Othman, Azlina (2018)
Papaya is one of the major fruits exported as well as favorite fruit among all ages. However, it is difficult for fruit sellers or consumers to identify the best quality of papaya f and to detect the amount of mature papaya in a short period of time. Thereore, a simple system is proposed to determine the fruit maturity by utilizing active Radio Frequency Identification (RFID) and Wireless Sensor Network (WSN). The main objective of this project is to determine the fruit maturity. An algorithm based on MATLAB has been developed using image processing toolbox to identify the color of the fruit. The color i analyzed by setting the average color, which must be over 400 pixels. Based on the results, he papaya can be categorized as mature when the color value exceeds 400 pixels and immature when the color value is less than 400 pixels. The accuracy of the proposed system is about 80% of which 8 of IO papaya are able to give good prediction. To determine the amount of mature fruit within a short period of time, RFID system has been applied by using Xbee Pro S2b as a medium of transmission. Several tests have been conducted to evaluate performance of the proposed system which are the data transmission in the indoor location and outdoor location. In terms of time and distance, it is proven that when the distance exceeds I OOm, the transmission is weak or no longer available. It can be concluded that, by combining image processing method with RFID technology, the maturity of fruits can be easily obtain at anywhere with reliable results.